The impact of Employee Training on Huawei innovation Performance in Shanxi Province, China - Liu, Xiaohua; Prompanyo , Manoch (International Journal of Multidisciplinary in Management and Tourism, 2021)
This paper finds the innovation gap and Huawei is a private enterprise with employees holding equity, and employees are the source of sustained vitality and driving force for Huawei's development and innovation. Therefore, this paper starts from employee training. Employee training has become one of the most important links for Huawei to achieve effective innovation. As the terminal department, Huawei authorized the experience stores(HAES), whose employees can more truly understand customers' needs. China's first Huawei 5G smart experience store has opened in Shanxi Province. The purpose was to research the impact of employee training on Huawei innovation performance in Shanxi Province, China; and to analyse validity, reliability, correlation analysis linear regression. The population is 9478 employees in HAES in Shanxi Province, including all technical research and development, product production, sales, service and a series of related employees. This paper adopted mix methods with in-depth interview and questionnaire survey, and SPSSAU is used for data analysis. The analysis results show that there is a positive impact between employee training on Huawei innovation performance. The conclusion is that they become the most important part of employee training and need to be constantly updated, including collaborative innovation culture and atmosphere, innovative service concept, innovation promotion and innovation service incentive mechanism, employees' enthusiasm, initiative and creativity, the promotion of brand culture, feedback Mechanism, etc.